Thomas Jefferson and the science of republican government : a political biography of notes on the state of Virginia - Klinghard, Daniel; Gish, Dustin (Cambridge University Press, 2017)
This analysis of Thomas Jefferson's only published work demonstrates the political aspirations behind its composition, publication and dissemination.